Naturalization of the absolute. The application of evolution’s explanatory mechanism to the study of religion - Kowalczyk-Purol, Kinga (Hybris, 2014)
The question which has troubled scholars for many decades (or even centuries) is the origin and function of religion. In this article, the author tries to sketch an outline of a new and promising paradigm in the study of religion, i.e. the evolutionary theories of religion. It is widely held belief that this enterprise should further provide an explanatory framework for an enormous amount of data about human religiosity. Such an aim requires giving an overview of the three fundamental Darwinian theories which pertain to this extremely multifaceted phenomenon. The sequence in the overview is like this: (a) a historical and conceptual background, (b) a sociobiological account, (c) a cognitive account, (d) a memetic account. The paper also comprises a short presentation of so-called co-evolutionary perspective, which integrates the above-mentioned outlooks, and some shortcomings of the whole evolutionary program of the study of religion.